2021
DOI: 10.1002/jcsm.12763
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the NLRP3/IL‐1β axis protects against sepsis‐induced cardiomyopathy

Abstract: Background Septic cardiomyopathy worsens the prognosis of critically ill patients. Clinical data suggest that interleukin‐1β (IL‐1β), activated by the NLRP3 inflammasome, compromises cardiac function. Whether or not deleting Nlrp3 would prevent cardiac atrophy and improve diastolic cardiac function in sepsis was unclear. Here, we investigated the role of NLRP3/IL‐1β in sepsis‐induced cardiomyopathy and cardiac atrophy. Methods Male Nlrp3 knockout (KO) and wild‐type (WT) mice were exposed to polymicrobial sepsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 48 publications
3
50
0
Order By: Relevance
“…Cecal ligation and puncture (CLP) surgery was performed in 12-to 16-week-old male Il6st cKO mice and WT littermate controls, as recently described. 10,25 Sham mice were treated identically except for the ligation and puncture of the cecum. The effects of AG490 treatment on sepsis-induced muscle atrophy were investigated in 20-week-old male C57BL/6J mice.…”
Section: Animal Model Of Polymicrobial Sepsismentioning
confidence: 99%
“…Cecal ligation and puncture (CLP) surgery was performed in 12-to 16-week-old male Il6st cKO mice and WT littermate controls, as recently described. 10,25 Sham mice were treated identically except for the ligation and puncture of the cecum. The effects of AG490 treatment on sepsis-induced muscle atrophy were investigated in 20-week-old male C57BL/6J mice.…”
Section: Animal Model Of Polymicrobial Sepsismentioning
confidence: 99%
“…Accordingly, septic Nlrp3-deficient mice showed a reduced activation of NF-κB, which was accompanied by a decrease in atrogin-1/MAFbx and MuRF1 expression when compared with wildtype littermate controls. Because Nlrp3 deletion reduces mortality and sepsis-induced end-organ damage, such as muscle failure [195], cardiomyopathy [250,251] and acute lung injury, pharmacological NLRP3 inhibition might be beneficial in sepsis. Indeed, positive effects were reported for the NLRP3-inhibitors hemin, which protected against cecal ligation and puncture (CLP)-induced acute lung injury in mice [252], and scutellarin as well as glyburide, which improved survival of mice with bacterial sepsis [253,254].…”
Section: Interleukin 1βmentioning
confidence: 99%
“…When exposed to diverse stimuli, such as LPS, TNF- α and IFN- γ , M1 macrophages are activated, and intracellular inflammatory and metabolic reprogramming pathways are activated, including STAT1, NF-κB and HIF-1 α axes, eventually promoting the generation of plentiful cytokines that damage cardiomyocytes and then induce cardiac dysfunction ( Y. Liu et al, 2017 ; Chen et al, 2021 ). Moreover, other bioactive factors, such as PGE2, TXB2 ( Amunugama et al, 2021 ), NO ( Jia et al, 2018 ) and NLRP3 ( Busch et al, 2021 ), are reported to facilitate inflammation progression and tissue injury during the course of sepsis. However, to date, the specific mechanisms responsible for SIC remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al, 2017;Chen et al, 2021). Moreover, other bioactive factors, such as PGE2, TXB2 (Amunugama et al, 2021), NO (Jia et al, 2018) and NLRP3 (Busch et al, 2021), are reported to facilitate inflammation progression and tissue injury during the course of sepsis. However, to date, the specific mechanisms responsible for SIC remain elusive.…”
Section: Introductionmentioning
confidence: 99%